(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article analyzes the theoretical foundations and didactic characteristics of learner-centered education, as well as the ways of improving it through innovative pedagogical technologies. The effectiveness of applying modern information and communication technologies, digital learning platforms, the modular-credit system, and interactive methods is scientifically substantiated, taking into account learners’ individual needs, abilities, and developmental dynamics within the educational process. In addition, the principles for enhancing learner-centered education are highlighted in the context of the ongoing reforms in Uzbekistan’s education system.